Impact of the Dual Deletion of the Mitochondrial Sirtuins SIRT3 and SIRT5 on Anti-microbial Host Defenses - Heinonen, Tytti; Ciarlo, Eleonora; Le Roy, Didier; Roger, Thierry (Frontiers in Immunology, 2019)
The sirtuins SIRT3 and SIRT5 are the main mitochondrial lysine deacetylase and desuccinylase, respectively. SIRT3 and SIRT5 regulate metabolism and redox homeostasis and have been involved in age-associated metabolic, neurologic and oncologic diseases. We have previously shown that single deficiency in either SIRT3 or SIRT5 had no impact on host defenses in a large panel of preclinical models of sepsis. However, SIRT3 and SIRT5 may compensate each other considering that they share subcellular location and targets. Here, we generated a SIRT3/5 double knockout mouse line. SIRT3/5 deficient mice multiplied and developed without abnormalities. Hematopoiesis and immune cell development were largely unaffected in SIRT3/5 deficient mice. Whole blood, macrophages and neutrophils from SIRT3/5 deficient mice displayed enhanced inflammatory and bactericidal responses. In agreement, SIRT3/5 deficient mice showed somewhat improved resistance to Listeria monocytogenes infection. Overall, the double deficiency in SIRT3 and SIRT5 has rather subtle impacts on immune cell development and anti-microbial host defenses unseen in single deficient mice, indicating a certain degree of overlap between SIRT3 and SIRT5. These data support the assumption that therapies directed against mitochondrial sirtuins, at least SIRT3 and SIRT5, should not impair antibacterial host defenses.